Pendampingan Pengisian SPT Tahunan Bagi Wajib Pajak Orang Pribadi - Miswaty Miswaty; Yanzil Azizil Yudaruddin; Dika Karlinda; Ranita Ramadhani; Tutik Yuliani; Amelia Dwi Anita; Eflin Lilis; Suryanti Simbolon (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Community service (PKM) as a tenant of academic responsibility, especially lecturers in the Accounting Study Program at the Faculty of Economics, Balikpapan University, in order to help individual taxpayers improve their ability to calculate and report taxes online. This PKM also hopes to support government programs in increasing revenue from the tax sector. Individual Taxpayers (WPOP) who have a NPWP do not always understand taxation. It is hoped that this service activity can help and provide understanding to taxpayers about taxation, including their obligations, reporting limits and how to fill out their annual SPT. The taxpayer problem that will be resolved in this activity is that there are many taxpayers in the city of Balikpapan who have not reported their annual SPT because they do not understand how to fill out the SPT. So taxpayers cannot fill in the Annual Income Tax SPT and report it incorrectly or do not report the SPT. The method applied to overcome this taxpayer problem is by providing training through public lectures which are held in collaboration with several lecturers in the accounting study program, Faculty of Economics, Balikpapan University, DJP employees and students who are members of the tax volunteers of the FE Uniba accounting study program. This activity is divided into 2 stages, namely the first session is a public lecture to socialize taxation to training participants and the second session is assistance in filling out the annual SPT. This community service activity is carried out to help WPOP who experience difficulties in filling out their Annual Tax Returns online, either through e-filling or e-form. In community service activities, the participants reached 28 WPOP from various professions. The results of this activity show that the majority of participants agree and strongly agree that this assistance is needed to help them report their Annual Tax Returns and fulfill their tax obligations.